Computer vision syndrome in teachers of a university of the province of Lima - Meneses Claudio, Brian Andreé (2023)
Virtual education has generated consequences at the visual level of people during the coronavirus pandemic since spending more time on the computer, it compromises the eye health of the person causing long-term visual problems, so its research objective is to determine the computer-related ophthalmic syndrome in teachers at a university of the province of Lima. It is a quantitative, non-experimental, descriptive, and cross-sectional study, with a total population of sixty-three teachers who answered a digital survey with socio-demographic data and the Computer Vision Syndrome Questionnaire (CVS-Q) instrument. In the results, we can observe the results of the computerized ophthalmic syndrome in teachers at a university in the province of Lima, where 51 (81%) of the teachers do not present computer vision syndrome, and 12 (19%) present computer vision syndrome. In conclusion, the population conducting virtual education should be educated as well as students about prevention measures for computer ophthalmic syndrome and its consequences.